Social determinants of participant recruitment and retention in a prospective cohort study of pediatric mild traumatic brain injury - Wells, Jordee M.; Galarneau, Jean-Michel; Minich, Nori M.; Cohen, Daniel M.; Clinton, Kameron; Taylor, H. Gerry; Bigler, Erin D.; Bacevice, Ann; Mihalov, Leslie K.; Bangert, Barbara A.; Zumberge, Nicholas A.; Yeates, Keith Owen (Frontiers in Neurology, 2022)
Background Prior studies have shown poor recruitment and retention of minoritized groups in clinical trials. Objective To examine several social determinants as predictors of consent to participate and retention as part of a prospective, longitudinal cohort study of children 8–16 with either mild traumatic brain injury (mild TBI) or orthopedic injury (OI). Methods Children and families were recruited during acute visits to emergency departments (ED) in two large children's hospitals in the midwestern United States for a prospective, longitudinal cohort study of children 8–16 with either mild TBI or OI. Results A total of 588 (mild TBI = 307; OI = 281) eligible children were approached in the ED and 315 (mild TBI = 195; OI = 120) were consented. Children who consented did not differ significantly from those who did not consent in sex or age. Consent rates were higher among Black (60.9%) and multi-racial (76.3%) children than white (45.3%) children. Among the 315 children who consented, 217 returned for a post-acute assessment (mild TBI = 143; OI = 74), a retention rate of 68.9%. Participants who were multi-racial (96.6%) or white (79.8%) were more likely to return for the post-acute visit than those who were Black (54.3%). Conclusions Racial differences exist in both recruitment and retention of participants in a prospective, longitudinal cohort of children with mild TBI or OI. Further work is needed to understand these differences to ensure equitable participation of minoritized groups in brain injury research.